The Formulation of Aloe Vera (Aloe chinensis Baker) and Calyx of Roselle Flower Petals (Hibiscus sabadariffa L.) For Making Fruit Leather - Estha Fresua; Maherawati Maherawati; Lucky Hartanti (FoodTech: Jurnal Teknologi Pangan, 2022)
Fruit leather is a diversification of jam products. The main ingredient of fruit leather is potential agricultural product. West Kalimantan is the largest supplier of aloe vera in Indonesian while rosella calyx contains pectin and acids as important factors in the making of fruit leather. The aim of this research is to find a formulation of fruit leather by aloe vera and roselle calyx which produce the best chemical and sensory characteristics. The research design uses a randomized block design one factor (formulation of aloe vera and rosella calyx) by five levels of treatment (80:20, 70:30, 60:40, 50:50, 40:60) and was repeat 5 times. The data obtained were statistically analyzed using ANOVA (α = 5%) and if followed by BNJ test (α = 5%). The results showed that the best formulation based on effectiveness index was aloe vera: roselle calyx (60:40) with a characteristic water content  35.46%; crude fiber content  0.71%; vitamin C content 75.68 mg / 100 g; pH 3.15; calcium content 28,2712 mg / 100 g; 16,16% sucrose. The sensory level produces a hedonic texture scale of 4.6 (likes), colors 4.7 (likes) and taste 4.43 (likes).